Monitoring the natural attenuation of a sewage sludge toxicity using the Allium cepa test - Mazzeo, Dânia Elisa Christofoletti [UNESP]; Fernandes, Thaís Cristina Casimiro [UNESP]; Levy, Carlos Emílio; Fontanetti, Carmem Silvia [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Elsevier, 2015)
Appropriate final disposal of sewage sludge (SS) generated by wastewater treatment plants (WWTP) has been considered a serious environmental problem, but also a viable alternative to be applied in agriculture, once SS is rich in organic matter and nutrients. However, SS can be a source of contamination of several toxic agents. Therefore, its use in agriculture requires special care to avoid possible damage to the environment and exposed organisms. Detoxification of toxic wastes can be performed using the monitored natural attenuation, which involves biological, physical and chemical processes that frequently occur in the environment. This study aimed to assess the feasibility of decontaminating SS after different periods of monitored natural attenuation. To this end, samples of SS and associations of soil/SS with proportions of 10, 25 and 50% SS were buried for 0, 2, 6 and 12 months in holes prepared in a place free of contamination. Allium cepa was used as an indicator to assess the efficiency of the natural attenuation process. According to chemical analysis, the SS samples presented a high concentration of m- and p-cresol, especially for samples analyzed after 0 or 2 months of natural attenuation. The microorganisms present in the SS belonged to 17 different genera of bacteria, which varied in the microbial composition among samples. Both, raw SS and aqueous SS extracts induced DNA damage in A. cepa, even when associated with soil. However, this effect was observed to decline during the attenuation period, although significant effects were detected for the highest tested concentration (100% SS) even at the end of this process. These results thus indicated the necessity of applying a stabilization process associating SS and soil for a period of at least 12 months and showed that the studied raw SS is not a viable material for use as a soil reconditioner, even after natural attenuation. A. cepa test proved to be a useful tool to assess the efficiency of SS detoxification process. Therefore, we suggest that the application of SS in agriculture should be approached with caution and that the SS must be previously submitted to methodologies that evaluate its toxic potential.
Keywords: Chromosomal aberration; Cytotoxicity; Genotoxicity; Micronucleus; Solid waste; Waste management